School-based collaborative reflection for professional learning: a case study of primary school teachers in Ethiopia. Issue 6 (2nd November 2022) - Taddese, Esayas Teshome; Rao, Congman
ABSTRACT: This qualitative case study explores the practices of school-based teacher collaborative reflection based on the experiences of Ethiopian primary school teachers. Guided by constructivist epistemology, data were collected via in-depth interviews, focus group discussions (FGDs) and document reviews, and field notes. The findings revealed that teachers are compelled to engage in school-based collaborative reflection for professional learning through mandatory collaborative teams. This sharply contrasts with teachers' long-standing norms of autonomy that appreciate independence and non-reliance. As a result, in order for a school-based collaborative practice to be reflective and successful, the tension between teacher autonomy and the need for collaboration must be resolved. Moreover, the findings disclosed that teacher collaborative reflection is a widely touted subject but less of a reality in the context of Ethiopian primary schools because of context-specific structural and cultural factors.